KAJIAN SIMBOLIK KRESNA WANDA RONDON PADA WAYANG KULIT PURWA GARAPAN SAIMONO AGUS SUBIANTORO - Sari, Yuni Prastika; Shokiyah, Nunuk Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2017)
This study examines focus on the symbolic meaning of shadow puppet Kresna wanda Rondon produced by Saimono Agus Subiantoro and background creation. This research is descriptive qualitative research. The validity of the data using triangulation data. Analysis of the data used is the analysis of the interaction with Saimono directly to find out the background of the creation of the work. To explain the meaning of the symbolic use of interpretation through symbols theory approach Susanne K. Langer.Â Keywords: Symbol, Krishna Wanda Rondon, Saimono